AN ANALYSIS OF EXPRESSIVE SPEECH ACT IN MOVIE ENTITLED LUCA BY ENRICO CASAROSA - Dia Indriyana; Sumardiono Sumardiono (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This study aims to analyse the kinds and forms of expressive speech acts in the movie entitled Luca. The researcher used qualitative descriptive method. The researcher watching movie, taking notes, organizing the data into several parts based on classification. The researcher collected and classified the data then make conclusion. The researcher used the validity triangulation data and triangulation theory to check validation. The result of the research showed that there were 9 kinds expressive speech acts; thank, apologizing, congratulation, greeting, wishes, attitudes, praising, blaming, and forgiving and there were 3 forms of expressive speech acts; direct literal speech act, indirect literal speech act, direct non-literal speech act.   Key words: Expressive Speech Acts, Luca Movie